2010
DOI: 10.5005/jp-journals-10005-1052
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Oral Hygiene Habits in Mentally Disabled Children

Abstract: BackgroundThe main factor related to gingival/periodontal problems in disabled individuals is the inadequacy of the plaque removal from the teeth. Motor coordination problems and muscular limitation in neuromuscularly disabled individuals along with the difficulty in understanding the importance of oral hygiene in mentally disabled individuals have resulted in the progression of inflammatory diseases.Case reportThis report describes a case of cerebral palsy child who developed gingival hyperplasia due to poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Complete oral prophylaxis and restorations of all carious teeth should also be done to reduce the colony forming units in the oral cavity. Postoperative follow up with proper guidance to parents/caregivers should be of utmost importance for long term success of treatment (Das et al, 2010). Pre and postoperative complications had occurred in first case report such as delayed reversal, difficult tracheal intubation, upper respiratory tract infections, laryngeal edema, Gastrointestinal effects such as constipation, aspiration of gastric contents, intraoral ulcerations (Wass et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Complete oral prophylaxis and restorations of all carious teeth should also be done to reduce the colony forming units in the oral cavity. Postoperative follow up with proper guidance to parents/caregivers should be of utmost importance for long term success of treatment (Das et al, 2010). Pre and postoperative complications had occurred in first case report such as delayed reversal, difficult tracheal intubation, upper respiratory tract infections, laryngeal edema, Gastrointestinal effects such as constipation, aspiration of gastric contents, intraoral ulcerations (Wass et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is imperative to provide oral health and hygiene related, diet counselling guidance to the caregiver before the discharge of the patient. Oral health related problems are very common in children with CP, hence, a multidisciplinary approach with active involvement of the pediatric dentist, the caregiver is required along with long term strategic follow ups should be done to improve the oral health quality of the patient and to promote good health and wellbeing of the patient (Das et al, 2010;Jaya et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The primary molars of these children were restored with stainless steel crowns because of the high degree of bruxism seen in these children leading to dental wear [27]. Dietary and home care counselling of the parents prior to discharge along with long term post-operative follow-up is key to successful management of these children [28]. In most instances due to the overall health related issues affecting the child the parents tend to ignore the oral health related issues until pain or discomfort affects the child functionally.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need for guidance and training of those responsible to promote oral health. 13 A randomized controlled trial conducted by Bozkurt et al found that patients with CP were found to have significant improvement in plaque levels and gingival health when their parents and caregivers used an electric toothbrush as opposed to a manual toothbrush. 14 Two studies provided evidence that children with CP were better able to brush their own teeth when they were given toothbrushes that had been individually modified mainly the length and size of the handle.…”
Section: Johsrmentioning
confidence: 99%